Temporal changes in artificial light exposure of marine turtle nesting areas. (24th January 2014) - Kamrowski, Ruth L.; Limpus, Col; Jones, Rhondda; Anderson, Sharolyn; Hamann, Mark
Abstract Artificial light at night poses a significant threat to multiple taxa across the globe. In coastal regions, artificial lighting close to marine turtle nesting beaches is disruptive to their breeding success. Prioritizing effective management of light pollution requires an understanding of how the light exposure of nesting areas changes over time in response to changing temporal and spatial distributions of coastal development. We analyzed multitemporal, satellite night‐light data, in combination with linear mixed model analysis, to determine broadscale changes in artificial light exposure at Australian marine turtle nesting areas between 1993 and 2010. We found seven marine turtle management units (MU), from five species, have experienced significant increases in light exposure over time, with flatback turtles nesting in east Australia experiencing the fastest increases. The remaining 12 MUs showed no significant change in light exposure. Unchanging MUs included those previously identified as having high exposure to light pollution (located in western Australia and southern Queensland), indicating that turtles in these areas have been potentially exposed to high light levels since at least the early nineties. At a finer geographic scale (within‐MU), nine MUs contained nesting areas with significant increases in light exposure. These nesting areas predominantly occurred close to heavily industrialized coastal areas, thus emphasizing the importance of rigorous light management in industry. Within all MUs, nesting areas existed where light levels were extremely low and/or had not significantly increased since 1993. With continued coastal development, nesting females may shift to these darker/unchanging 'buffer' areas in the future. This is valuable information that informs our understanding of the capacity and resilience of marine turtles faced with coastal development: an understanding that is essential for effective marine turtle conservation.